The incidence of hepatocellular carcinoma and clearance of hepatitis B surface for CHB patients in the indeterminate phase: a systematic review and meta-analysis - Liu, Min; Zhao, Taixue; Zhang, Yuting; Zhang, A-Mei; Geng, Jiawei; Xia, Xueshan (Frontiers in Cellular and Infection Microbiology, 2023)
Background Nearly 30%–40% of patients with chronic hepatitis B do not fall into any of the traditional natural history classification and thus are classified as indeterminate. However, it is unclear whether patients in the indeterminate phase (IP) are at a higher risk for hepatocellular carcinoma (HCC) than those in the defined phases (DP) and would benefit from antiviral therapy. We performed a systematic review and meta-analysis of HCC incidence and HBsAg clearance among patients in the IP versus DP. Methods We defined the clinical phases as per the AASLD 2018 hepatitis B guidance. We searched PubMed, Embase, Medline, and Web of Science for relevant studies that reported HCC incidence or HBsAg clearance in IP versus DP patients published between January 2007 and March 2023. Annual HCC incidence and HBsAg clearance rates were pooled using a random/common-effects model. Results We analyzed data from 14 studies, comprising 7798 IP patients (222 patients developed HCC and 239 achieved HBsAg clearance) and 10,725 DP patients. The pooled annual HCC incidence was 2.54 cases per 1,000 person-years (95% CI, 1.14–4.39) and HBsAg clearance rate was 12.36 cases per 1,000 person-years (95% CI, 10.70–14.13) for the IP patients. IP patients were associated with significantly higher HCC incidence risk (RR = 1.64, 95% CI, 1.34–2.00) and slightly lower annual HBsAg clearance rate (RR = 0.83, 95% CI, 0.70–0.99) than the DP patients. In addition, HBeAg-negative IP patients (2.31%; 95% CI, 0.87–4.45) showed a significantly higher HCC incidence than those who were HBeAg positive (0.00%; 95% CI, 0.00–0.99) (p< 0.001). The Asia-Pacific region IP patients (4.30%; 95% CI, 2.07–7.27) were also associated with a higher HCC incidence versus Europe (0.05%; 95% CI, 0.00–1.39) (p< 0.001). However, there were no significant differences between different strategies (treated vs. untreated: 2.56%; 95% CI, 1.01–4.63 vs. 1.61%; 95% CI, 0.00–5.81, p = 0.09), and heterogeneity was substantial across the studies (I2 = 89%). Conclusion The systematic review and meta-analysis showed a high HCC incidence and low HBsAg clearance among patients in the IP, especially for HBeAg-negative patients and the Asian population. We emphasize that future multicenter prospective cohort studies or randomized trials are needed to verify if expanding antiviral therapy for patients in the IP is associated with reduced HCC risk or good treatment outcomes.